The CPEB translational regulator, Orb, functions together with Par proteins to polarize the Drosophila oocyte - Barr, Justinn (PLoS Genet, 2019)
orb is a founding member of the CPEB family of translational regulators and is required at multiple steps during Drosophila oogenesis. Previous studies showed that orb is required during mid-oogenesis for the translation of the posterior/germline determinant oskar mRNA and the dorsal-ventral determinant gurken mRNA. Here, we report that orb also functions upstream of these axes determinants in the polarization of the microtubule network (MT). Prior to oskar and gurken translational activation, the oocyte MT network is repolarized. The MT organizing center at the oocyte posterior is disassembled, and a new MT network is established at the oocyte anterior. Repolarization depends upon cross-regulatory interactions between anterior (apical) and posterior (basal) Par proteins. We show that repolarization of the oocyte also requires orb and that orb is needed for the proper functioning of the Par proteins. orb interacts genetically with aPKC and cdc42 and in egg chambers compromised for orb activity, Par-1 and aPKC protein and aPKC mRNA are mislocalized. Moreover, like cdc42(-), the defects in Par protein localization appear to be connected to abnormalities in the cortical actin cytoskeleton. These abnormalities also disrupt the localization of the spectraplakin Shot and the microtubule minus-end binding protein Patronin. These two proteins play a critical role in the repolarization of the MT network.